Budaya Organisasi dan Peran Audit Internal: Mediasi Pendidikan dan Kesadaran Keberlanjutan di Perguruan Tinggi - Evi Ekawati; Yetri Martika Sari (Value : Jurnal Manajemen dan Akuntansi, 2026)
This study examines the influence of organizational culture on the internal audit role in sustainability at State Islamic Religious Universities (PTKIN), with sustainability awareness and education programs as mediating variables. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 74 lecturers and educational staff at three PTKINs in Lampung and South Sumatra provinces ranked in the top five of UI GreenMetric 2024. Results show that organizational culture positively influences sustainability awareness, education programs, and the internal audit role in sustainability. Education programs positively influence the internal audit role and significantly mediate the relationship between organizational culture and the internal audit role. Sustainability awareness, however, neither directly influences nor mediates this relationship, reflecting an attitude-behavior gap where awareness rooted in Islamic values tends to manifest in individual behavior rather than institutional oversight capacity. These findings highlight that education programs serve as the critical transmission mechanism converting cultural commitment into concrete internal audit capacity at PTKIN.